Factors influencing the participation of groups identified as underserved in cervical cancer screening in Europe: a scoping review of the literature - Greenley, Rachel; Bell, Sadie; Rigby, Samuel; Legood, Rosa; Kirkby, Victoria; McKee, Martin, the CBIG-SCREEN Consortium (Frontiers in Public Health, 2023)
Background: Cervical cancer is a preventable and inequitably distributed disease. Screening plays a vital role in prevention, but many women face barriers to participation. The aim of this scoping review, undertaken to inform the co-design of interventions to equitably increase uptake was to: (1) identify barriers and facilitators to cervical cancer screening for underserved populations, (2) identify and describe the effectiveness of interventions aimed at improving participation in cervical cancer screening amongst underserved groups in Europe. Methods: Qualitative, quantitative, and mixed methods studies undertaken in Europe and published after 2000 were included. Four electronic databases were searched to identify peer-reviewed publications that examined barriers and facilitators of access to cervical cancer screening and interventions to increase screening uptake. Titles and abstracts were screened, full text reviewed, and key findings extracted. Data on barriers and facilitators were extracted and analysed using pre-defined categories, micro, meso, and macro, relating to levels of activity in the health system. Within these categories, themes were identified, and their distribution across population groups was recorded. Data on interventions were grouped according to the same pre-defined levels. All findings are in accordance with (PRISMA) guidelines. Results: 34 studies met the inclusion criteria for the research question on barriers and facilitators across vulnerable and underserved populations. Eight studies met the eligibility criteria for intervention studies. Conclusions: The majority of barriers and facilitators were described at the meso- and micro-levels, i.e., within specific screening services and communities. A wide array of barriers and facilitators was identified, indicating a diversity of challenges and opportunities relating to screening access. Consistent with these patterns, the majority of interventions targeted the micro and meso levels of the system. Overall, the findings of this study indicate that implementation should focus on: (1) reducing screening barriers, (2) increasing public awareness, and (3) providing patient reminders and measures to promote engagement by healthcare providers.